Dictionary of Islamic Names : Derived from Qurʼan, Ahadith, Seerah and History with Meaning and Pronunciation - Compiled by Shaukat Ali Hareeri and Ikram Tahir, Muhammad (Riyadh Darussalam, 2009)
The first lesson given to Adam after his creation was the knowledge of names, which established his superiority over the Angels, and became the reason for their prostration to him. Although the Holy Qur'an does not give the names that Adam was taught, it does say that the earliest form of knowledge imparted to man by his Creator was the knowledge of names. The first lesson also established the identity of objects and humon beings from the beginning. Besides the identity of the individual, names also reflect the religion, moral values, nation and country of persons. Therefore, neonate babies should be given good names. Although several books on this subject are available in the market but this book is different for the following qualities: * The beautiful Names of Allah, the Almighty, and the prophet (s.a.w.) are given along with one reference at least to make them more interesting and useful. * Names of the prophet's (s.a.w.) companions are also given in a large number, although some of them are not so meaningful yet they may be adopted to express affiliation with the pious figures. * Quality of the names has been preferred to the quantity against the norm of the books of names.
Keywords: Names, Personal--Islamic -- Names Dictionaries